2022
DOI: 10.1007/s12662-021-00795-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving reduced physical activity during COVID-19 lockdown is related to lower quality of life: a cross-sectional study with young adults

Abstract: Physical activity and social participation are positively related to mental health and represent resources that strengthen individuals’ resilience. However, the measures aiming to contain the coronavirus disease 2019 (COVID-19) pandemic included restrictions regarding these health resources. For many people, stay-at-home orders had a negative effect on mental health and health-related behaviors such as physical activity. Young adults seem to be a particularly vulnerable group. The study aimed to examine the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…They deteriorated by around 10% from 1975 to 2003 [ 7 , 8 ], before stagnating at a relatively low level until today [ 9 , 10 ]. Negative impacts on physical, psychosocial and mental health are the likely consequences [ 11 , 12 ]. Physical activity and fitness interventions have only been moderately effective in this context [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They deteriorated by around 10% from 1975 to 2003 [ 7 , 8 ], before stagnating at a relatively low level until today [ 9 , 10 ]. Negative impacts on physical, psychosocial and mental health are the likely consequences [ 11 , 12 ]. Physical activity and fitness interventions have only been moderately effective in this context [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among those selected study, most of the study found cross-sectional study (Patra et al , 2020; Phillipou et al , 2020; Ripon et al , 2020; Sankar et al , 2020; López-Moreno et al , 2020; Al-Domi et al , 2021; Ali et al , 2021; Sińska et al , 2021; Vu et al , 2021; Wei et al , 2021; Ceulemans et al , 2021; Chi et al , 2021; Hammami et al , 2021; Jonikas et al , 2021; Madan et al , 2021; Niermann, Bollenbach and Kanning, 2022; Lorenzoni et al , 2022; Mekkawy, 2022), retrospective study (Błaszczyk-Bębenek et al , 2020; Almandoz et al , 2021; Valenzise et al , 2021), literature review (Neira et al , 2021; Andersson et al , 2022), review and mini-review (Arora and Grey, 2020; Bennett et al , 2021; Scapaticci et al , 2022), longitudinal study (Zhang et al , 2020a, 2020b; Herle et al , 2021; Sebastian et al , 2021) and online survey included (Vally and Helmy, 2021; Wilson et al , 2021; Woodruff et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Mental health, dietary habits and physical activity were studied in (Ripon et al , 2020; Ali et al , 2021; Chi et al , 2021; Wei et al , 2021; Wilson et al , 2021; Woodruff et al , 2021; Lorenzoni et al , 2022), Mental health and weight-related behavior included in (Almandoz et al , 2021; Madan et al , 2021; Valenzise et al , 2021), physical activity and motivation (Andersson et al , 2022; Niermann, Bollenbach and Kanning, 2022), health behavior (Arora and Grey, 2020; Al-Domi et al , 2021; Woodruff et al , 2021), lifestyle and dietary habits (Sankar et al , 2020; Bennett et al , 2021; Madan et al , 2021; Neira et al , 2021; Scapaticci et al , 2022), mental health status in pregnant and lactating (Zhang et al , 2020a, 2020b; Ceulemans et al , 2021), eating behavior (Błaszczyk-Bębenek et al , 2020; Phillipou et al , 2020; Herle et al , 2021; Sińska et al , 2021; Vu et al , 2021), mental health and behavioral health disorder (Hammami et al , 2021; Jonikas et al , 2021; Vally and Helmy, 2021; Mekkawy, 2022), food habits (López-Moreno et al , 2020) and school closure and screen (Patra et al , 2020; Woodruff et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations